Commemorating the Past for the Sake of the Present: Public Uses of the Past and Politics of Memory in the Bicentenary of the Consummation of Mexican Independence - Verdú Sánchez, Inmaculada (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
Commemorations exert a great attraction both at the level of historiographical reflection, leading to the emergence of new consensuses and interpretations thanks to the production of research, and in the political sphere, as they are the ideal occasion to deploy memory policies with the intention of legitimising a particular political and national project. Thus, historians and political authorities share a great interest in commemorations, although they do not always agree on how to take advantage of commemorative events. The Bicentenary of the consummation of Mexican Independence in 2021 is an ideal scenario for reflection on the problematic of the public uses of the past.
Keywords: commemoration; bicentenary; Mexico; independence; public uses of the past